2016
DOI: 10.1002/pssb.201552617
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and structural properties of AlGaNAs alloys grown by chemical beam epitaxy

Abstract: We correlate the structural properties of aluminium‐based dilute nitrides to their electrical properties. The effect of annealing on the carrier density and the mobility is measured on chemical beam epitaxy grown Al0.05Ga0.95N0.005As0.995 alloys. Both parameters increase with the annealing temperature due to the disappearance of N–C and N–H–VGa complexes. After annealing, a mobility of 60 cm2 V−1s−1 for a hole concentration of 1 × 1019 cm−3 are measured, which is similar to the values reported on GaAs with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…We also showed that, by reducing the defect density, annealing improves the mobility of Al y Ga 1Ày N x As 1Àx alloys up to values similar to those reported on GaAs for the same carrier concentrations. 29 Furthermore, morphology studies suggested that Al distributes the N atoms in the layer more uniformly by incorporating them next to an Al site instead of forming clusters. 28 Pits observed on the GaN x As 1Àx surface and attributed to N clusters become smaller and more uniformly distributed in the presence of B10% Al.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that, by reducing the defect density, annealing improves the mobility of Al y Ga 1Ày N x As 1Àx alloys up to values similar to those reported on GaAs for the same carrier concentrations. 29 Furthermore, morphology studies suggested that Al distributes the N atoms in the layer more uniformly by incorporating them next to an Al site instead of forming clusters. 28 Pits observed on the GaN x As 1Àx surface and attributed to N clusters become smaller and more uniformly distributed in the presence of B10% Al.…”
Section: Introductionmentioning
confidence: 99%